2017
DOI: 10.1017/s003329171700085x
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the role of neuroticism in suicidal ideation and suicide attempt among women with major depressive disorder

Abstract: Background Prior research consistently demonstrates that neuroticism increases risk for suicidal ideation, but the association between neuroticism and suicidal behavior has been inconsistent. Whereas neuroticism is recommended as an endophenotype for suicidality, the association of neuroticism with attempted suicide warrants clarification. In particular, prior research has not distinguished between correlates of attempted suicide, correlates of suicidal ideation, and correlates of comorbid psychopathology. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 66 publications
(142 reference statements)
2
23
0
1
Order By: Relevance
“…However, without the presence of Depression symptoms in the predictive equation, Neuroticism was a protective factor against suicide. While research on neuroticism and Suicidal Ideation has found elevated neuroticism scores in people who report Suicidal Ideation, studies on neuroticism and attempted suicide have shown conflicting results (Rappaport et al., ). Cox, Enns, and Clara (), in the National Comorbidity Survey, did not find an association between neuroticism and prior suicide attempts, while other studies have reported an association (Fergusson et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, without the presence of Depression symptoms in the predictive equation, Neuroticism was a protective factor against suicide. While research on neuroticism and Suicidal Ideation has found elevated neuroticism scores in people who report Suicidal Ideation, studies on neuroticism and attempted suicide have shown conflicting results (Rappaport et al., ). Cox, Enns, and Clara (), in the National Comorbidity Survey, did not find an association between neuroticism and prior suicide attempts, while other studies have reported an association (Fergusson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rappaport, Flint, and Kendler () examined the association of neuroticism with Suicidal Ideation and attempted suicide in a large sample of Chinese women (5,864 women with major depressive disorder and 5,783 women without major depressive disorder). The authors found that elevated neuroticism was associated with an increased risk of Suicidal Ideation, while elevated neuroticism was associated with a decreased risk for attempted suicide among participants who reported Suicidal Ideation.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the nine symptoms of MDD (American Psychiatric Association, 2013), suicidal ideation may also be effectively targeted with the UP. As detailed in Bentley and colleagues (2017b), leading theoretical models point to the experience of intense negative affect as a key factor in the development and maintenance of suicidal thoughts and behaviors (e.g., Baumeister, 1990;Beck, 1986;Joiner, 2005;Linehan 1993;Shneidman, 1993); indeed, neuroticism is associated with suicidal ideation even when adjusting for comorbid clinical disorders (e.g., Handley et al, 2012;Mandelli et al, 2015;Rappaport et al, 2017). Additionally, clinical observation (e.g., O'Connor, 2003;Selby, Anestis, & Joiner, 2007) and initial empirical support (e.g., Kleiman et al, 2018) suggest that suicidal thoughts and behaviors may serve similar functions to the aversive, avoidant reactions to negative affect that maintain emotional disorders.…”
Section: Applicability and Preliminary Evidence For Suicidal Ideationmentioning
confidence: 99%
“…Depression-induced work absenteeism, loss of work productivity, decreases in work competence and increases in health-related expenditures are also serious social problems (18) , suggesting that depression is not only a mental burden for one individual but also a public health problem with respect to health promotion and management. Additionally, prior research studies have consistently demonstrated that depression increases the risk for suicidal ideation (19,20) . Although a national suicide prevention programme was implemented in the early 2000s, suicide remains the fifth most common cause of death among Korean adults as of 2017 (21) .…”
mentioning
confidence: 98%